Written monuments in old Prussian - Letas Palmaitis (Knygotyra)
The appearance of historically testified written monuments in Old Prussian is connected with the beginning of the Christianization of Old Prussian tribes, i.e., with the aggression of the Catholic Teutonic Order against the Old Prussians and other peoples of the Baltic region in the 13th century.